Bacterial Infections in Cirrhosis - Guadalupe Garcia-Tsao (Canadian Journal of Gastroenterology)
Hospitalized patients with cirrhosis are at increased risk of developing bacterial infections, the most common being spontaneous bacterial peritonitis (SBP) and urinary tract infections. Independent predictors of the development of bacterial infections in hospitalized cirrhotic patients are poor liver synthetic function and admission for gastrointestinal hemorrhage. Short term (seven-day) prophylaxis with norfloxacin reduces the rate of infections and improves survival and should therefore be administered to all patients with cirrhosis and variceal hemorrhage. Cirrhotic patients who develop abdominal pain, tenderness, fever, renal failure or hepatic encephalopathy should undergo diagnostic paracentesis, and those who meet the criterion for SBP (eg, an ascites neutrophil count greater than 250/mm3) should receive antibiotics, preferably a third-generation cephalosporin. In addition to antibiotic therapy, albumin infusions have been shown to reduce the risk of renal failure and mortality in patients with SBP, particularly in those with renal dysfunction and hyperbilirubinemia at the time of diagnosis. Patients who recover from an episode of SBP should be given long term prophylaxis with norfloxacin and should be assessed for liver transplantation.